2017
DOI: 10.3126/jnarc.v3i1.17269
|View full text |Cite
|
Sign up to set email alerts
|

Yield Evaluation of Nutrient-rich Potato Clones in High Hill of Nepal

Abstract: A study was conducted to evaluate the yield of nutrient-rich potato clones in high-hill districts: Dolakha and Jumla of Nepal during the years 2013 and 2014, respectively. Fourteen potato clones were tested as on-station and on-farm experiments at both districts, and those fourteen clones were compared to 'Lady Rosita' and 'Jumli Local' respectively as the check varieties in the first year experiment, 2013. Eight promising clones were selected from the first year experiment, and were evaluated and compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 4 publications
3
10
0
Order By: Relevance
“…Tuber yield is a complex trait, affected by genotype and environmental factors (Struik & Wiersema, 1999). Luitel et al (2016) reported a marketable tuber yield variation of 7.6 to 24.0 tha -1 at high hills of Nepal and similar tuber yield variation were reported on potato by different researchers in Nepal (Luitel et al 2017a;Gainju et al 2019). In addition to the genotypic effect, differences in tuber size, plant spacing and weather variations could have caused the yield variation among the genotypes (Masarirambi et al 2012).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Tuber yield is a complex trait, affected by genotype and environmental factors (Struik & Wiersema, 1999). Luitel et al (2016) reported a marketable tuber yield variation of 7.6 to 24.0 tha -1 at high hills of Nepal and similar tuber yield variation were reported on potato by different researchers in Nepal (Luitel et al 2017a;Gainju et al 2019). In addition to the genotypic effect, differences in tuber size, plant spacing and weather variations could have caused the yield variation among the genotypes (Masarirambi et al 2012).…”
Section: Discussionmentioning
confidence: 77%
“…Seifu and Betewulign (2017) also reported a significant difference in total tubers plant -1 among potato varieties. Tuber weight is an important yield component of potato that contributes to total tuber yield (Morena et al 1994;Luitel et al 2017a). Variation in marketable tuber weight among the genotypes may be due to genetics.…”
Section: Discussionmentioning
confidence: 99%
“…Potato is an important crop for both hills and terai of Nepal [7]. It is an important crop for food security in the high hills of Nepal contributing substantially to the livelihood of resource poor farmers in the mountains [8].…”
Section: Introductionmentioning
confidence: 99%
“…The genotypes varied in their source, tuber color, flesh color, tuber shape, eye depth, maturity, and yield (Table 1a and Table 1b Luitel et al, 2017;4 NPRP 20164 NPRP , 20174 NPRP , 20185 NPRP 2018;6 Upadhyay, 2017 Potato genotypes were harvested in the second week of May 2019 after they reached their full harvesting maturity. Storage experiment was conducted on the third week of May 2019 and continued to the second week of August 2019 (80 days).…”
Section: Potato Genotypesmentioning
confidence: 99%
“…These tubers were spread on the experimental floor randomly and genotypes were separated with wooden sticks. Nutrient-rich genotypes CIP 393073.179 and CIP 395112.32 were included to determine their potentiality of storage (Luitel et al, 2017).…”
Section: Potato Genotypesmentioning
confidence: 99%